Assessment of recent GOCE-based global geopotential models and EGM2008 in Niger Republic - Ibrahim Yahaya, Salissou; El Azzab, Driss (Geodesy and Cartography, 2019)
In this study, we assessed recent GOCE-based Global Geopotential Models (GGMs) and EGM2008 in Niger. The combined GGMs EIGEN_6C4, GECO and EGM2008 were evaluated up to their maximum degree and order (d/o) 2,190 to select the one for gravity database densification. The following pure satellite GGMs were assessed for the modelling of the long and medium wavelengths in geoid computation: GGM05G, ITU_GGC16, EIGEN_6S4v2 and the fifth releases from direct (DIR5), space-wise (SPW5) and time-wise (TIM5) approaches. The GGMs are compared to terrestrial gravity data and geoid heights from GNSS/Levelling points before and after applying spectral enhancement method (SEM) by residual terrain model (RTM) for combined models and by RTM and the coefficients of selected combined GGM for pure satellite models. The agreements of combined GGMs with terrestrial gravity data and GNSS/Levelling points, in terms of root mean square (RMS) are about 4.88 to 5.02 mGal and 0.14 to 0.16 m, respectively. EIGEN_6C4 was selected as it showed the best performance in terms of geoid height differences and the probability of 3-sigma rule for gravity anomaly differences. At d/o 200, DIR5 showed a good agreement with terrestrial gravity data (5.04 mGal) and GNSS/Levelling points (0.15 m) after applying SEM, it was then retained. All GOCE-based models exhibited a good performance in long and medium wavelengths confirming the good recovery of the gravity field by the spatial gravity mission in these spectral bands.